The change in biocomfort zones in the area of Muğla province in near future due to the global climate change scenarios - Cetin, Mehmet; Sevik, Hakan; Koc, Ismail; Zeren Cetin, Ilknur (Elsevier BV, 2023)
It is inevitable that the global climate change, which has important effects on the climate throughout the world, would have significant effects on the biocomfort zones. Hence, how global climate change will change the biocomfort zones should be determined and the data to be obtained should be used in urban planning projects. In the current study, SSPs 245 and SSPs 585 scenarios were taken as a basis, and the potential effects of global climate change on the biocomfort zones in Muğla province, Türkiye were investigated. Within the scope of the present study, the current status of biocomfort zones in Muğla and their possible conditions in years 2040, 2060, 2080, and 2100 were compared using DI and ETv methods. At the end of the study, it was estimated that, according DI method, 14.13% of Muğla province are in cold zone, 31.96% in cool zone, and 53.71% in comfortable zone. According to the SSPs 585 scenario, together with the increase in temperature, the cold and cool zones will totally disappear in year 2100, comfortable zones will decrease to 31.22%, and approx. 68.78% of the province will be in hot zone. According to the calculations made using ETv method, Muğla province currently consists of moderately cold zones by 2%, quite cold zones by 13.16%, slightly cold zones by 57.06%, and mild zones by 27.79%. Based on the SSPs 585 scenario for the year 2100, it is projected that Muğla will consist of slightly cool zones by 1.41%, mild zones by 14.42%, and comfortable zones by 68.06%, besides warm zones by 16.11% which are not present at this moment. This finding suggests that especially the cooling costs will increase and the air-conditioning systems to be used will negatively affect the global climate change through the energy consumption and the gases used.
Keywords: Etv Method; Climate Change; Temperature; Mugla; Biocomfort; Cold Temperature; Biocomfort; Global Climate Change; Etv Method; Climate Scenarios; Mugla; Global Climate Change; Seasons; Climate Scenarios; Thermal Comfort; Management; Responses; Density; 15. Life on land; 13. Climate action; 11. Sustainability